On the thermal performance of radiative stagnation-point hybrid nanofluid flow across a wedge with heat source/sink effects and sensitivity analysis - Chakraborty, Anomitra; Saadeh, Rania; Qazza, Ahmad; Zomot, Naser; Janapatla, Pranitha; Khan, Umair; Qraywi, Mohammad; Muhammad, Taseer (Frontiers in Materials, 2024)
The present article aims to examine the thermal performance and the sensitivity analysis of a 𝐺𝑟𝑂 -𝑇𝑖𝑂 2 / water hybrid nanofluid in presence of different shapes of the nanoparticle along with heat absorption and thermal radiation effects over a wedge geometry. Analysing the effects of heat generation and radiation effects is one of the key studies conducted by most of the researchers in various nanofluid flows over some required geometries but a combined study of these effects was yet to be studied over a moving wedge and it defines the novelty of the work. Similarity transformations are implemented to the governing equations for obtaining the final set of non-dimensional equations which are solved using bvp4c code in MATLAB. The results obtained were in close agreement to the published results. Nusselt number reduced for an increment in heat source parameter (𝑄) and it augmented for an increasing Hartree pressure gradient (𝛽) and thermal radiation parameter (𝑅𝑑). The sensitivity is statistically analysed for the variations in radiation effect, heat source and pressure gradient parameters on the Nusselt number. The high values for 𝑅 2 = 99.99% and 𝐴𝑑𝑗 𝑅 2 = 99.96% validates the ANNOVA results obtained using BBD model in Response Surface Methodology (RSM) with 14 degrees of freedom. The input parameters 𝑅𝑑 and 𝛽 shows positive sensitivity while 𝑄 shows negative sensitivity towards the skin-friction. The Nusselt number proves to be most sensitive towards pressure gradient parameter. TiO2 along with Graphene (Gr) and its derivative forms are gaining much importance for their wide applications in oil and petroleum industries. Thus, this study contributes to lubrication purposes, emulsion stabilizers, oxalic acid removal, anticorrosive properties etc.